Phase portraits of bernoulli quadratic polynomial differential systems - Llibre, Jaume; Pereira, Weber F. [UNESP]; Pessoa, Claudio [UNESP] (My University, 2020)
In this article we study a new class of quadratic polynomial differential systems. We classify all global phase portraits in the Poincaré disk of Bernoulli quadratic polynomial differential systems in R2 .
Keywords: Bernoulli equation; Phase portrait; Poincaré disk